(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
In today’s competitive business environment, even small improvements in productivity and efficiency can have a huge impact on company’s profitability. Companies can improve operations and quality by controlling / improving lead time and reducing waste. Lean is an operational management technique used to systematically improve the efficiency and quality of processes / services. The concept is being used in mining organizations across the globe and resulted into improved productivity, safety & morale of the employees. PCMM is maturity model used for HR / people related process improvement. PCMM consists of best of the HR & People management practices used in IT & Technology industry. This paper explores the possibility of implementation of a new lean & PCMM-based framework in mining industries that will help in optimal utilization of human capital. This framework will have positive business impact and result into benefits. Companies that excel at implementing such best practices throughout the organization will find themselves at a great advantage in a world where humans and machines working together outperform either humans or machines working on their own.